A comparison of platform and sea-bed mounted flow measurement instrumentation for SME PLAT-I. Issue 2 (September 2022) - Frost, C.; Togneri, M.; Jeffcoate, P.; Lake, T.; Boake, C.; Starzmann, R.; Williams, A.
No abstract available